Effect of Hidoxyl Substitution on Cobalt Phthalocyanine as Catalyst for Oxygen Reduction Reaction Using DFT Method - Wulandari, Hepi; Kasmui, Kasmui (Indonesian Journal of Chemical Science, 2021)
Oxygen Reduction Reaction (ORR) is an important reaction in the cathode and the main limiting factor of performance for fuel cells. The process of dioxygen (O2) reduction is not easy, due to its electronic configuration and high activation energy barrier, thus ORR needs to be catalyzed. Today there have been many developed catalysts such as phthalocyanine metal. CoPc compounds modified with hydrogen atoms are substituted by the OH group into CoPc(OH)16 to increase the activity of catalysts and the stability of the molecular structure of these catalysts in ORR applications. The purpose of the study was to explain the ORR reaction path in CoPc(OH)16 molecule, calculate DFT calculations using Material Studio software with DMol3 modules, PBE and PW91 exchange-correlation functions, and DNP basis set to determine structure optimization, with adsorption energy of O2, H2O, OH, H2O2, and H2O molecules on the surface of CoPc(OH)16 molecules. The results of CoPc(OH)16 optimization cause an increase in electron affinity values, decrease chemical hardness values, increase molecular reactivity and also increase binding energy between atoms. While adsorption results by CoPc(OH)16 amplify O2 adsorption energy and H2O2 adsorption energy, weakening OH adsorption energy. Through optimization results during the adsorption process also proves the CoPc(OH)16 catalyst through the two-electron reduction pathway in the ORR process. Calculations using the PW91 function produce lower adsorption energy than the PBE function, so the calculation using the PW91 function is better.